The Malaysian agricultural industry in the new millennium: issues and challenges - Bakar, B.B. (2009)
Malaysian agriculture is characterized by dualism, viz. smallholder’s sector with an average farm size of 1 - 2 ha, and the plantation-based estate sector with farm sizes in excess of 500 ha. This dichotomy in agricultural industry placed great economic emphasis on cash crops, namely oil palm, rubber, and cocoa although sizeable acreages of the arable lands are planted with food crops like rice, pepper, fruit orchards, vegetables, and herbs. The industry has evolved from a stereotypic Third World peasantry economic entity to the vibrant third engine of economic growth contributing no less than US$5.63, 6.34, 7.75, and 8.48 billion to the national GDP in 2003, 2005, 2007 and 2008, respectively. Agriculture remains an important part of the national economy in the new millennium for the increasingly burgeoning populace with the challenge to provide both food security and safety, and sustainable development and wealth creation. The primary issues besieging Malaysian agriculture in the new millennium include ensuring food security and food safety for the populace with parallel and determined effort to sustain, and where possible, increase exports of agricultural produce. Albeit the apparent decline of agricultural sector to the Malaysian national economy, agricultural development in Malaysia, faces three major challenges in new millennium, viz. (i) Persistence of poverty among the rural farming community; (ii) Food insecurity for the traditional agricultural systems; (iii) Continuing and perennial pressure on the deterioration of the natural resource base; (iv) Labour-intensive plantation agriculture which faces the valgary of foreign labour; (v) Low returns from agricultural investment; (vi) Stagnating prices of commodities; (vii) High costs of land, and (viii) Often volatile market forces. The Malaysian government re-emphasis and renewed interest in agriculture especially for food production principally to off-set the unhealthy trend of steady increase in food imports augurs well in promoting agricultural development in the country. This coupled with the opening of new economic zones in Peninsular Malaysia, Sabah and Sarawak supported by the fledging government-based administrative, research, technical and extension services, and augmented by those in the private sector call for new strategize plans from the view point of natural resources sustainability and environmental safety. The already-in-place New Agricultural Policies serve as the framework for agricultural development in the country in the new millennium. These NAPs were promulgated with the principal thrusts areas: (a) Meeting national food requirements – through large food production by the private sector; (b) Enhancing competitiveness and profitability in agriculture and forestry promoting globally competitive industries in agriculture and forestry, developing world competitive outlook and an export culture; (c) Capitalizing on the product value-chain by reorientation from commodity-based to product-based production and marketing, capital and technology intensive agricultural production system and less labour intensive enterprises as well as cultivation of high-value 338 crops and forest species; (d) Enhancing the integrated development of the food and industrial crop; (e) Strengthening requisite economic foundation, upgrading quality of human resources, development of indigenous R&D capabilities and technology, namely modern infrastructure, business support services, financing and incentives and an enabling institutional framework; and (f) Adopting and emphasizing sustainable development rules and regulations, and strengthening incentives.